ANALISIS PEMASARAN PISANG KEPOK DI DESA BUMI SEJAHTERA KECAMATAN KALIORANG KABUPATEN KUTAI TIMUR (Marketing Analysis of Kepok Banana in Bumi Sejahtera Village, Kaliorang Subregency, East Kutai Regency) - SETYAWAN SETYAWAN; SITI BALKIS (Universitas Mulawarman (University of Mulawarman), 2021)
Marketing is all activities related to the delivery of products or services from producer to consumer. Kepok banana is one of the most cultivated variety of banana because of the high of price and demand. The purposes of this research were to find out the marketing channel, marketing costs, margin, share, profit, and marketing efficiency of kepok banana. This research was conducted in Bumi Sejahtera Village, Kaliorang Subregency, East Kutai Regency from April to July 2020. The determination of banana farmer samples used simple random sampling with the number of respondents as many as 31 respondents and the determination of samples of marketing institutions used snowball sampling method with the number of respondents as many as 21 respondents. The results of research showed that there were 3 marketing channels of kepok banana namely levels channel of 2, 3, and 4. The marketing costs of 2, 3, and 4 channels were IDR1,441.35 comb-1; IDR1,521.53 comb-1; and IDR1,811.11 comb-1, respectively. The marketing margin of 2, 3, and 4 channels were IDR7,062.50 comb-1; IDR7,175.00 comb-1; and IDR7,500.00 comb-1, respectively. The marketing profit of 2, 3, and 4 channels were IDR5,651.20 comb-1; IDR5,653.47 comb-1; and IDR5,688.89 comb-1 , respectively. The marketing share of 2, 3, and 4 channels were 45.67%; 43.72%; and 42.31%, respectively. Marketing channels of kepok banana in Bumi Sejahtera Village are efficient because the efficiency value was < 50%.